2010
DOI: 10.3109/00207454.2010.535935
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-1 Regulates Neurite Outgrowth and Neuronal Migration From Organotypic Cultured Dorsal Root Ganglion

Abstract: Insulin-like growth factor-1 (IGF-1) is a neurotrophic factor and plays an important role in promoting axonal growth from neurons. Whether IGF-1 could promote neurite outgrowth and neuronal migration of dorsal root ganglion (DRG) explants in vitro remains unknown. In the present study, organotypic rat DRG explant culture model was established. Using this unique culture system, outgrowth of neurites from the peripheral nerve attached to DRG explant and migration of neurons from DRG explant to the peripheral are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Furthermore, our studies demonstrated that IGF‐I plays a critical role in regulating the exit of neuroblasts from the subventricular zone (SVZ) and the incorporation of new neurons into the adult olfactory bulb (OB), in part through the activation of the PI3K/AKT pathway . However, IGF‐I effects on hippocampal cell migration/positioning were not reported .…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, our studies demonstrated that IGF‐I plays a critical role in regulating the exit of neuroblasts from the subventricular zone (SVZ) and the incorporation of new neurons into the adult olfactory bulb (OB), in part through the activation of the PI3K/AKT pathway . However, IGF‐I effects on hippocampal cell migration/positioning were not reported .…”
Section: Introductionmentioning
confidence: 95%
“…IGF-1 and BDNF have been implicated to play important role in the nervous system and neurogenesis, under both healthy and inflammatory conditions, by regulating cell growth, differentiation, migration, survival and neurite outgrowth [56][58]. For example, IGF-1 was shown to regulate neurite outgrowth and cell migration from rat dorsal root ganglion explants in a dose-dependent manner (0–20 nM) [59]. Similarly, BDNF was found to significantly enhance cortical neurite outgrowth in a dose-dependent (0–100 pg/mL) manner when cultured in the presence of immature astrocytes, suggesting potential applications in axonal regrowth strategies after spinal cord injury [60].…”
Section: Resultsmentioning
confidence: 99%
“…The number of nerve fiber bundles extended from the DRG explants was counted as previously described (Xiang et al, 2011). Briefly, nerve fiber bundles extended from the DRG explants as far as 200 µm from the edge of a quarter of each DRG explant were counted in each sample.…”
Section: Determination Of Neurite Outgrowth From Drg Explantsmentioning
confidence: 99%